Развитие альтернативных источников энергии - Вороновский, Игорь Богданович; Вороновський, Ігор Богданович; Voronovskyi, Ihor (My University, 2019)
RU: Рассмотрена проблема поиска альтернативных возобновляемых источников энергии. Показаны основные тенденции влияния современной энергетики на окружающую среду. Произведен анализ современного энергетического баланса мира. Указаны основные этапы развития энергетической отрасли. Отмечены страны-лидеры в области альтернативной энергетики. Обозначены положительные и отрицательные стороны применения альтернативных источников энергии. Рассмотрена Европейская программа развития энергетики на возобновляемых источниках энергии, приведены некоторые достижения в области альтернативной энергетики высокоразвитых стран, в частности энергетическая политика Швейцарии. Выделены основные идеи и изобретения ученых, в которых находится ключ к настоящей энергетической независимости всех людей на Земле. Начало эры безтопливной энергетики относят к 1892 году, когда Никола Тесла изобрел резонансный трансформатор и получил на выходе многократно превышающую входную энергию. Указаны причины умалчивания данного факта. Очерчены перспективы использования альтернативных источников энергии. UK: Розглянуто проблему пошуку альтернативних поновлюваних джерел енергії (ПДЕ). Показані основні тенденції впливу сучасної енергетики на навколишнє середовище. Зроблено аналіз сучасного енергетичного балансу світу. Вказані основні етапи розвитку енергетичної галузі. Позначено країни-лідери в галузі альтернативної енергетики. Позначені позитивні і негативні сторони застосування ПДЕ. Розглянуто Європейську програму розвитку енергетики для ПДЕ, наведені деякі досягнення в галузі альтернативної енергетики розвинених країн, зокрема енергетична політика Швейцарії. Виділено основні ідеї та винаходи, вчених в яких знаходиться ключ до енергетичної незалежності. В одному з прогнозних сценаріїв розвитку світової енергетики стверджується, що вже до 2020 р за рахунок ПДЕ може бути задоволено до 20% всіх світових потреб в комерційній енергії. Цей показник може досягти 50%, тоді як в даний час за рахунок ПДЕ покривається приблизно 2% світових потреб в первинних енергоресурсах. Цілком природно, що ці оцінки повинні розглядатися лише з точки зору можливостей ПДЕ, а не як прогноз розвитку. Проте вони свідчать про величезний потенціал ПДЕ. Ми живемо у величезному океані енергії. Все: кожен атом, кожна елементарна частинка знаходиться в постійному русі, завжди обертається, навіть в холодному темному порожньому просторі - абсолютному вакуумі. Це те, що сучасна фізика називає квантовим потоком вакууму. Древні називали його ефіром, метафізика - енергією життєвої сили. Тепер це доведено як теоретично, так і математично. Вже не стоїть питання про те, чи існує енергія нульової точки Початок ери безпаливної енергетики відносять до 1892 році, коли Нікола Тесла винайшов резонансний трансформатор і отримав на виході багаторазово перевищену вхідну енергію. Вказані причини замовчування цього факту. Окреслено перспективи використання альтернативних джерел енергії. EN: The problem of searching for alternative renewable energy sources is considered. The main trends of the influence of modern energy on the environment are shown. The analysis of the modern energy balance of the world is made. The main stages of the development of the energy sector are indicated. Leading countries in the field of alternative energy are noted. Positive and negative aspects of the use of alternative energy sources are indicated. The European program for the development of energy on renewable energy sources is considered, some achievements in the field of alternative energy of highly developed countries, in particular the energy policy of Switzerland, are listed. The basic ideas and inventions, scientists in which the key to real energy independence of all people on the Earth is located, are singled out. Energy is the ability of the electromagnetic field of the universe to react, revaccinate and redistribute the results of all interactions to zero potential or equilibrium state. In one of the projected scenarios for the development of the world energy, it is argued that by 2020 up to 20% of all world commercial energy needs can be met by RES. This figure can reach 50%, while currently about 2% of the world's primary energy needs are being covered by renewable energy sources (RES). It is only natural that these assessments should be considered only in terms of the potential of RES and not as a prognosis for development. However, they do testify to the enormous potential of RES. We live in a vast ocean of energy. Everything: every atom, every elementary particle is in constant motion, always rotating, even in the cold dark empty space - absolute vacuum. This is what modern physics calls quantum vacuum flow. The ancients called it ether, metaphysics - the energy of the vital force. Now this is proven both theoretically and mathematically. The question is whether there is zero point energy The beginning of the era of zero-fuel power is attributed to the year 1892, when Nikola Tesla invented the resonant transformer, and received output many times higher than the input energy. The reasons for not mentioning this fact are indicated. Prospects for the use of alternative energy sources are outlined.
Розвиток альтернативних джерел енергії
Development of alternative energy sources
Keywords: эфир; возобновляемые источники энергии; солнечная энергетика; ветровая энергетика; свободная энергия; альтернативный источник; ефір; поновлювані джерела енергії; сонячна енергетика; вітрова енергетика; вільна енергія; альтернативне джерело; ether; renewable energy sources; solar energy; wind power; free energy; alternative source